Engineering Homochiral Metal-Organic Frameworks for Heterogeneous Asymmetric Catalysis and Enantioselective Separation - Liu, Yan; Xuan, Weimin; Cui, Yong (Advanced materials (Weinheim), 2010)
Owing to the potential applications in technological areas such as gas storage, catalysis, separation, sensing and nonlinear optics, tremendous efforts have been devoted to the development of porous metal‐organic frameworks (MOFs) over the past ten years. Homochiral porous MOFs are particularly attractive candidates as heterogeneous asymmetric catalysts and enantioselective adsorbents and separators for production of optically active organic compounds due to the lack of homochiral inorganic porous materials such as zeolites. In this review, we summarize the recent research progress in homochiral MOF materials, including their synthetic strategy, distinctive structural features and latest advances in asymmetric heterogeneous catalysis and enantioselective separation. Homochiral porous metal‐organic frameworks (MOFs) are particularly attractive candidates as heterogeneous asymmetric catalysts and enantioselective adsorbents and separators for production of optically active organic compounds. This review summarizes the recent research progress in homochiral MOF materials, including their synthetic strategy, distinctive structural features and applications in enantioselective catalysis and separation.